A New Technique Using Low Volumes: A New Technique to Assess the Molluscicidal Activity Using Low Volumes. (29th August 2017) - Santos, José Augusto Albuquerque; Cavalcante, Viviane Paixão; Rangel, Leonardo da Silva; Leite, João Claudio Vitória Atico; Faria, Robson Xavier
Abstract : Schistosomiasis is a disease endemic in several states of Brazil. The population control of the transmitter mollusks is done with Bayluscide WP 70®, in the control programs. OMS preconize molluscicidal assays using Becker with 500 mL of final volume, restringing the number of natural products and synthetic drugs to be tested in function of high quantity of material necessary. A new technique to assess the toxic effects for Biomphalaria sp. is the purpose of this work, for developing adaptation for this aquatic organism, using a low volume of test solution in 24-well plates. We used Biomphalaria glabrata (10–12 mm size) in a static system, consisting of the following components: Becker containing 10 snails or 24-well plates where snails were individualized for a volume of 2 mL per well for 24 and 48 hours. For the assays, we added aqueous solutions of Bayluscide WP 70, at a concentration of 1–5 mg/L, distilled water, and 1% dimethyl sulfoxide. Data were evaluated using Kappa's coefficient, Z factor validation, and comparison study. This technique to assess the toxic effect has proven to be a useful tool to detect lethal and sublethal effects, which could be used as a new evaluation protocol.